Micturition in the toilet compared with bedpan in laboring Nulliparas: a randomized controlled trial - Maherah Kamarudin; Wen Kiat Chong; Mukhri Hamdan; Aizura Syafinaz Adlan; Rahmah Saaid; Peng Chiong Tan (BMC, 2022)
Abstract Background Bladder overdistension in labor may lead to prolonged postpartum urinary retention. We hypothesized that nulliparas mobilizing to toilet is more likely to achieve satisfactory micturition. Methods One hundred sixteen (58 in each arm) term nulliparas in labor with filled bladders were randomized to mobilizing to the toilet or using bedpan to micturate. Primary outcome was satisfactory micturition defined as ultrasound derived post-void bladder volume < 150 ml. Following unsatisfactory micturition, participants crossover to the opposed intervention. Participants were catheterized if after crossover, residual bladder volume was ≥250 ml. Results Satisfactory micturition rates were 55/58 (95%) vs. 43/58 (74%) RR 1.28 95%CI 1.08-1.51 NNTb 4.8 95%CI 3.0-12.4 P = 0.008, failure to micturate 1/58 (2%) vs. 8/58 (14%) RR 0.13 95%CI 0.02-0.97 NNTb 8.3 95%CI 4.6-38.7 P = 0.047. After cross over following unsatisfactory bladder voiding, satisfactory micturition rates were 0/3 (0%) vs 13/15 (87%) P = 0.024, bladder catheterization rates were 3/58 (5%) vs. 2/58 (4%) RR 95%CI 1.5 (0.26-8.65) P = 0.648, maternal satisfaction with allocated intervention 55/58 (95%) vs. 9/58 (16%) RR 95%CI 6.1 (3.3-11.2) NNTb 95%CI 1.3 (1.1-1.5) P <  0.0001 and preference for mobilizing to the toilet if micturition was needed again during labor 55/58 (95%) vs. 53/58 (92%) for mobilizing to the toilet compared to bedpan use arms respectively. Labor and neonatal outcomes were similar. Conclusion Satisfactory micturition was more frequently achieved with mobilization to the toilet than bedpan use. Women in both arms overwhelmingly prefer to mobilize to the toilet to urinate. Trial registration This study was registered with ISRCTN on 17/07/2019 with trial identification number: ISRCTN17787339 . First participant was recruited on 31/07/2019. The last patient was recruited on 18/12/2019.